Efficacy and safety of single-dose pregabalin in preoperative pediatric sedation - Wafiya Mahdy; Khaled Saad; Eman F Gad; Islam Shabaan; Abd-; Mohamed Ezzat; Noha A Afify (Wolters Kluwer Medknow Publications, 2024)
Introduction: This study aimed to investigate the anxiolytic and sedative effects of a single oral dose of 5 mg/kg pregabalin in pediatric patients undergoing elective surgery. It also assessed potential adverse effects and its impact on bispectral index (BIS) responses. Materials and Methods: This prospective randomized clinical trial enrolled 60 pediatric patients undergoing minor elective surgery. Patients were randomly assigned to receive either oral pregabalin (5 mg/kg) or a placebo one hour before induction of anesthesia. Anxiety levels were assessed using the Visual Analog Scale for Anxiety (VAS-A), and sedation levels were evaluated using the Ramsay Sedation Scale (RSS). Results: Pregabalin premedication significantly reduced preoperative anxiety, as indicated by lower VAS-A scores compared to the control group. Sedation levels, measured using the RSS, were significantly higher in the pregabalin group at various time points post-dose. During intubation, skin incision, and recovery, BIS responses were significantly lower in the pregabalin group. Conclusion: The use of single-dose pregabalin preoperatively in children recorded a significant decrease in anxiety and achieved a state of sedation without an increase in adverse effects.